The influence of college students’ psychological resilience on problem solving: based on eye tracking technology - Xu, Zhenguo; Du, Wenxiu; Zhao, Huaiyan; Liu, Qing; Xie, Wanli (Frontiers in Psychology, 2025)
IntroductionThe digital intelligence era has put forward new requirements for cultivating innovative talent, and problem solving ability is one of the key abilities for the cultivation of innovative talents.MethodsUsing eye tracking technology, this study explored the impact of college students’ psychological resilience on problem solving. A mixed experimental design (psychological resilience level × difficulty of questions) was employed, combining eye movement data, emotion observation record sheet, and retrospective oral reports. The differences in problem solving strategies of 24 college students in C programming were analyzed from multiple perspectives.ResultsThe study found that: (1) Eye movement behavior: Students with high psychological resilience exhibited longer total fixation duration, more regression counts, and greater pupil diameter changes during complex tasks. They showed comprehensive coverage and logical exploration of the stem and option areas, optimizing cognitive resource allocation through in-depth information processing. In contrast, students with low psychological resilience demonstrated shorter total fixation duration, fewer regression counts, and smaller pupil diameter changes, exhibiting “cognitive narrowing” and disordered exploration. (2) Problem solving strategies: Students with high psychological resilience employed strategies such as “segmental disassembly” and “secondary validation,” while students with low psychological resilience tended to use “random trial and error” or abandoned the task. (3) Emotion management: Students with high psychological resilience were emotionally stable, while students with low psychological resilience were prone to abandoning the task due to anxiety.DiscussionThis study offers a new perspective for exploring the impact of psychological resilience of college students on problem solving and provides scientific and practical guidance for enhancing college students’ problem solving abilities.